Peremoha velikoji žovtnevoji socialistyčnoji revoljuciji na Ukrajini. U 2ch t.t ("Naukova dumka", 1967)
AN Ukrajins'koji RSR. Instytut istoriji. 1: Avtory: S.M. Korolivs'kyj, M.A. Rubač i M.I. Suprunenko. 392 stor